PEMIKIRAN DAN BUDAYA MASYARAKAT TRADISIONAL CINA DALAM CERPEN â€œPERSEMBAHAN TAHUN BARUâ€ KARYA LU XUN - Neni Kurniawati (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2007)
: Literature is often considered as a reflection of societyâ€™s real life. It also depicts some lifeâ€™s aspect such as social, culture, thought, and belief. In Lu Xunâ€™s â€œNew Yearâ€™s Sacrificeâ€, those aspects are represented in words, sentences, and paragraphs. To get a deeper comprehension of it, people need to understand signs and symbols which author used. This paper aims to explain how literature can describe Chinese traditional culture and thought, especially about women, with semiotic approach by identifying any sign used in it. The result of this research shows that Chinese women are inferior in society. They are not worthy unless able to bear a son, so the continuation of the husbandâ€™s family can be preserved. Besides, women in China have to live with so many rules and obligations that society has created for them.